Gut Microbial Dysbiosis Is Associated With Profibrotic Factors in Liver Fibrosis Mice - Wan, Sizhe; Nie, Yuan; Zhang, Yue; Huang, Chenkai; Zhu, Xuan (Frontiers in Cellular and Infection Microbiology, 2020)
Background and Aims: Continuous development will evolve into end-stage liver disease. Profibrotic factors NOX4 and RhoA participate in the activation of HSC and accelerate the development of liver fibrosis. Abnormal intrahepatic metabolism during liver fibrosis interferes with intestinal homeostasis through the liver—gut axis. Methods: Wild-type (WT), NOX4 knockout, RhoA expression inhibition C57BL/6 mice were randomly divided into 6 groups as follows: control group, CCl4 group, NOX4−/− group, AP group, RhoAi group, and FA group. Results: The results of alpha-diversity suggest that the diversity and abundance of intestinal flora in liver fibrosis mice is lower than that in normal mice, but there is some recovery in liver fibrosis mice with NOX4 or RhoA intervention. The flora structure showed that the intestinal flora of the control group, NOX4−/− group, AP group, RhoAi group, and FA group belonged to one type, while the intestinal flora of the CCl4 group belonged to another type. In addition, analysis of the composition of the flora at the level of the phylum and genus also suggested the decline in Firmicutes and Lactobacillus caused by liver fibrosis has partially restore in the liver fibrosis mice with NOX4 or RhoA intervention. In terms of functional prediction, the “Secondary metabolites biosynthesis, transport and catabolism,” “Infectious diseases,” and “Xenobiotics biodegradation and metabolism” signaling pathways are mainly enriched in liver fibrosis mice, and the “Energy production and conversion,” “Defense mechanisms,” and “Carbohydrate metabolism” signaling pathways are mainly enriched in the NOX4 and RhoA intervention groups. Conclusion: In the case of liver fibrosis, the intestinal flora is disordered, and the disorder is related to NOX4 and RhoA. This study provides theoretical support for a better understanding of the underlying mechanisms of liver fibrosis development.